Brain MR imaging in acute hyperammonemic: Case report - Soukaina WAKRIM, MD; Adel El MEKKAOUI, MD; Othmane BENLENDA, MD; Khalila NAINIA, MD; Hicham NASSIK, MD (Radiology Case Reports, 2022)
Acute hyperammonemic encephalopathy is rare and generally is not widely known; only a few pediatric cases were found in the literature. These lesions’ clinical presentation differs significantly so they can mimic other lesions. In this case report, we discuss a 5-year-old boy who presented with generalized seizures and was unconscious in an apyretic context, for which she had a cranial computed tomographic and magnetic resonance imaging, both objectified an acute hyperammonemic encephalopathy resulting from an enzyme deficiency. Magnetic resonance imaging revealed lesions throughout the cortex, with the perirolandic and occipital cortices spared. This distribution of cerebral signal abnormalities on magnetic resonance imaging with an abrupt and profound neurological disorder is secondary to hyperammonemic. The knowledge of the magnetic resonance imaging results of this entity is essential to accelerate the diagnosis, and treatment, also to prevent sequelae.